Current knowledge on the effects of environmental contaminants in early life nutrition - Street, Maria E.; Shulhai, Anna-Mariia; Rotondo, Roberta; Giannì, Giuliana; Caffarelli, Carlo (Frontiers in Nutrition, 2023)
Abstract Breast milk represents the optimal source of feeding for newborn, in terms of nutritive compounds and useful properties involved in the immunological, metabolic, organic, neurological well-being. This biological fluid also contains environmental contaminants. Formulas through contact in bottles and cup and complementary feeding can also be contaminated. We focus on endocrine-disrupting chemicals, xenoestrogens that activate or antagonize hormonal receptors, and on indirect food additives, especially in infancy. We summarize the effects on immune system, gut microbiota and metabolism . Exposure to endocrine-disrupting chemicals and indirect food additives may induce tissue inflammation and polarize lymphocytes, increase proinflammatory cytokines, promotes allergic sensitization, and microbial dysbiosis, activate nuclear receptors and increase the incidence of allergic, autoimmune and metabolic diseases. These findings pave the way to strategies to prevent contamination of milk and to limit maternal and infant exposure before pregnancy.